A Rare and Fatal Complication of a Self-Limiting Infection: A Case Report on Dengue Associated Hemophagocytic Lymphohistiocytosis (Bangladesh Journal of Medicine, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening medical condition characterized by hyperphagocytosis secondary to an inappropriate over-activation of macrophages and lymphocytes that driven by excessive cytokines production which resulted in cellular destructions. It can arise de novo as a result of an autosomal recessive genetic disorder, or in the background of an infection, malignancy or autoimmune disease. Dengue fever is one of the uncommon causes of infection related secondary HLH. Here, we present a case of a Dengue associated HLH which was successfully treated with intravenous methylprednisolone and immunoglobulin G. In conclusion, the purpose of this case report is to illustrate the importance of early recognition and prompt initiation of the appropriate treatment for HLH suspected patient whom otherwise has high mortality rate.Bangladesh J Medicine July 2019; 30(2) : 93-95